The Effectiveness of Quizizz Application in Teaching Reading Comprehension - Mahaswary, Arjuna Nisrina; Tusino, Tusino; Ngafif, Abdul (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Reading comprehension is an important basic skill in English language learning, yet many students find it a difficult and uninteresting activity. This study aims to determine the effectiveness of using the Quizizz application in improving students’ reading comprehension skills. This study used a quantitative approach with a pre-experimental design of one-group pretest-posttest type. The samples in this study were 36 grade X students at SMAN 5 Purworejo in the 2024/2025 school year. Data were collected through multiple choice tests given before and after treatment. The treatment was carried out through the use of the Quizizz application as a digital learning media for five meetings. The data were analyzed using the paired sample t-test through the JASP program. The results showed a significant difference between the pre-test and post-test scores, with a significance value of 0.009 (p < 0.05). This finding shows that the use of Quizizz has a positive and significant effect on students’ reading comprehension skills. It can be concluded that Quizizz is an effective learning medium, not only as an evaluation tool, but also as a means of presenting reading material in a more interactive and motivating manner. Moreover, these findings contribute to the growing evidence supporting game-based learning tools in EFL reading instruction.